Sustainability and financial inclusion in microfinance institution research: A bibliometric and thematic analysis - Abdamia, Noranita; Abdullah, Mohd Fahmy; Lai., W. S (International Journal of Accounting, Finance and Business, 2026)
Microfinance institutions (MFIs) occupy a central but long-debated position in contemporary discourse on poverty reduction and sustainable development. After three decades of growth in the microfinance industry, cross-cutting research at the intersection of sustainability and financial inclusion within this field remains highly fragmented, with no fully formed systematic research lineage. To fill this gap, this study combines bibliometric methods and thematic analysis to synthesize MFI-related literature indexed in Scopus between 1996 and 2026. Following the PRISMA 2020 protocol, the study screens and retains 209 valid articles, uses BiblioSpy® to complete data processing and visualization, and covers five core categories of indicators. This study yields three core findings. First, academic output in the field has surged sharply after 2020, with the policy demand for inclusive finance and institutional resilience amplified by the COVID-19 pandemic as the core catalytic factor. Second, financial inclusion serves as the conceptual anchor of the field, linking three major research trajectories. Third, India contributes the largest number of published articles, while studies led by scholars from the United States and the United Kingdom lead in citation counts, exposing the asymmetry in knowledge production between the Global North and Global South. Emerging research directions such as digital finance are currently reshaping the boundaries of this field, and this study can provide effective support for relevant researchers, journal editors, and development practitioners.